THE LEGAL STUDIES OF TRUCKING AND WAREHOUSING IN SUPPORTING THE SMOOTHNESS OF OUTFLOW AND INCOMING GOODS AT THE PORT - Sulistiowati S; Saida Rusdiana (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2017)
AbstractThis legal study discusses the provision of trucking and warehousing of goods services and services at the port. This study is intended to address issues related research problems and directions arrangements in the provision of trucking and warehousing of goods services and services at the port. This study uses empirical juridical approach of practices in the truck transportation of goods and warehousing services in the port, while the results of the study are presented in the form of descriptive analysis. The study results conclusion that it is necessary for institutional capacity of port authorities as the organizer of the cultivated commercially port so as to perform the function of government in the harbor. Port Authority set the capacity of the service, organizing auctions and provision of related services to cooperate with trucking and warehousing services provider in the harbor. IntisariKajian hukum ini membahas mengenai penyediaan jasa truk angkutan barang dan jasa pergudangan di pelabuhan. Kajian ini dimaksudkan untuk menjawab permasalahan penelitian terkait permasalahan dan arah pengaturan dalam penyediaan jasa truk angkutan barang dan jasa pergudangan di pelabuhan. Kajian ini menggunakan pendekatan yuridis empirik dari praktek penyediaan jasa  truk angkutan barang dan jasa pergudangan di pelabuhan, sedangkan hasil penelitian disajikan dalam bentuk deskriptif analitis. Hasil kajian diperoleh kesimpulan bahwa diperlukan peningkatan kapasitas kelembagaan otoritas pelabuhan sebagai penyelenggara pelabuhan yang diusahakan secara komersial sehingga mampu menjalankan fungsi pemerintahan di pelabuhan. Otoritas Pelabuhan menetapkan kapasitas layanan, menyelenggarakan lelang penyediaan jasa terkait dan melakukan kerjasama penyedia jasa trucking dan warehousing di pelabuhan.